The Silent Risks of Sleepless Nights: Can short sleep duration be considered a significant risk factor for hypertension? - A literature review - Marcel Chudzikowski; Patryk Dudek; Klaudia Łuczak; Agnieszka Pawlik; Justyna Pięta; Agata Prokopiuk; Joanna Prus; Hanna Sitarek; Adrianna Tabeau; Wiktoria Ulicka (Journal of Education, Health and Sport)
Introduction and purpose